Performance Evaluation of Drainage Systems in Coastal Areas Using Storm Water Management Model: Case Study - Milad, Tandya Afilda; Maulana, Mahendra Andiek; Savitri, Yang Ratri (Newinera Publisher, 2026)
This study analyzes the performance of the urban drainage system in the Sringin Watershed, Semarang City, in response to rainfall runoff and evaluates the effectiveness of pump operation for flood mitigation. The assessment was carried out using a hydrologic and hydraulic modeling approach based on the Storm Water Management Model, supported by rainfall frequency analysis and spatial data processing. Design storms with ten‑year and twenty‑five‑year return periods were developed and applied to simulate system behavior under scenarios without pumps and with pump capacities of ten cubic meters per second and twenty‑five cubic meters per second. The results show that both return periods produce similar hydrologic responses, with peak inflow discharges ranging from fifty‑two to fifty‑five cubic meters per second and maximum storage volumes without pumping reaching forty‑six to forty‑seven percent of total capacity. The operation of a ten cubic meter per second pump effectively maintains water levels below the full‑storage elevation, while a twenty‑five cubic meter per second pump primarily accelerates drainage without significantly improving peak‑level control. These findings indicate that the ten‑year return period combined with a ten cubic meter per second pump provides the most efficient and practical design basis for current conditions, whereas the twenty‑five‑year return period is more suitable for evaluating extreme scenarios and long‑term resilience needs.